Infections after T‐replete haploidentical transplantation and high‐dose cyclophosphamide as graft‐versus‐host disease prophylaxis. Issue 2 (April 2015) - Crocchiolo, R.; Bramanti, S.; Vai, A.; Sarina, B.; Mineri, R.; Casari, E.; Tordato, F.; Mauro, E.; Timofeeva, I.; Lugli, E.; Mavilio, D.; Carlo‐Stella, C.; et al.
Abstract: Background: Recently, a platform of T‐cell replete haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) using post‐transplant cyclophosphamide (Cy) has shown high reproducibility and acceptable safety profile. Method: This prospective cohort analysis allowed us to collect data on infections among 70 consecutive recipients of haplo‐HSCT affected by various hematologic malignancies. Results: After a median follow‐up of 23 months, cumulative incidence of viral infections was 70% (95% confidence interval [CI] 59–81) at 100 days and 77% (95% CI 67–87) at 1 year; 35 of 65 patients at risk had CMV reactivation (54%) and the rate of polyomavirus‐virus‐associated cystitis was 19% (13/70). Cumulative incidence of bacterial and fungal infections at 1 year were 63% (95% CI 51–75) and 12% (95% CI 4–19), respectively. Of note, only 1 invasive fungal infection occurred beyond 1 year after transplant (day +739). Conclusion: In conclusion, despite a high rate of viral infections in the early period, present data suggest a satisfactory infectious profile after T‐cell replete haplo‐HSCT using post‐transplant Cy. These results may help clinicians to improve both prophylactic and therapeutic antimicrobial strategies in this emerging haploidentical setting.